Pengaruh Corporate Social Responsibility, Ukuran Perusahaan, dan Capital Intensity Terhadap Tax Avoidance - Khoirunnisa Heriana, Putri; Nuryati, Tutty; Rossa, Elia; Marinda Machdar, Nera (CV. Lafadz Jaya, 2023)
The purpose of this research is to analyze the theory that explains the effect of corporate social responsibility, company size, and capital intensity on tax avoidance. This study uses a literature review method. This study presents the theoretical basis, other explanatory variables and research results from previous literature. Supporting variables that influence tax avoidance consist of corporate social responsibility, company size, and capital intensity. These results indicate a different relationship between corporate social responsibility, company size, and capital intensity on tax avoidance so that no agreement is reached. This study provides a more comprehensive description of the phenomena that occur.